Significant improvement of organic solar cells with ternary additives - Wang, Minshuai (Frontiers in Physics, 2024)
Organic photovoltaics (OPVs) are gaining traction as a cost-effective and scalable alternative to conventional silicon-based solar cells, owing to their lightweight, flexibility, and tunable optical and electrical properties. Despite these advantages, the performance of OPVs is frequently hindered by non-optimal phase-separated morphologies that limit charge transport and extraction. A promising avenue to enhance the power conversion efficiency (PCE) of OPVs involves the incorporation of ternary additives, which have been shown to significantly refine the morphology of organic semiconductor blends. These additives promote the formation of a fibrillar-like nanoscale interpenetrating network, enhancing charge separation and transport. The dual-connected morphology achieved through ternary additives is crucial for improving the PCE. Additionally, the parallel bulk-heterojunction model formed by ternary additives has been instrumental in elucidating the photovoltaic parameters and understanding the effects of cascading heterojunction formation. Notably, block copolymer additives as one of ternary additives have demonstrated potential in stabilizing mixed donor-acceptor morphologies, leading to more efficient charge transfer. This review will explore the role of ternary additives in optimizing the morphology of OPVs and their impact on device performance, highlighting the mechanisms of block copolymer additives.